Differential measurement of electron ejection after two-photon two-electron excitation of helium - Straub, Michael; Ding, Thomas; Rebholz, Marc; Borisova, Gergana; Magunia, Alexander; Lindenblatt, Hannes; Meister, Severin; Trost, Florian; Wang, Yimeng; Palutke, Steffen; Braune, Markus; Düsterer, Stefan; et al. (Physical review letters, 2022)
We report the measurement of the photoelectron angular distribution of two-photon single-ionization near the 2p2 1De double-excitation resonance in helium, benchmarking the fundamental nonlinear interaction of two photons with two correlated electrons. This observation is enabled by the unique combination of intense extreme ultraviolet pulses, delivered at the high-repetition-rate free-electron laser in Hamburg (FLASH), ionizing a jet of cryogenically cooled helium atoms in a reaction microscope. The spectral structure of the intense self-amplified spontaneous emission free-electron laser pulses has been resolved on a single-shot level to allow for post selection of pulses, leading to an enhanced spectral resolution, and introducing a new experimental method. The measured angular distribution is directly compared to state-of-the-art theory based on multichannel quantum defect theory and the streamlined R-matrix method. These results and experimental methodology open a promising route for exploring fundamental interactions of few photons with few electrons in general.
Gesehen am 14.11.2022